Proteomic analysis of Trichoderma harzianum secretome and their role in the biosynthesis of zinc/iron oxide nanoparticles - Micaela B. Gallo; Araceli N. Bader; Andrés Torres-Nicolini; Vera A. Alvarez; Verónica F. Consolo (Scientific Reports, 2025)
Abstract The fungal green synthesis of nanoparticles (NPs) has gained great interest since it is a cost-effective and easy handling method. The process is simple because fungi secrete metabolites and proteins capable of reducing metal salts in aqueous solution, however the mechanism remains largely unknown. The aim of this study was to analyze the secretome of a Trichoderma harzianum strain during the mycobiosynthesis process of zinc and iron nanoparticles. Different profiles of proteins secreted by the fungus grown in the culture media or in the aqueous filtrate were observed through SDS‒PAGE and LC‒MS/MS analysis identifying 99 and 304 proteins, respectively. Particularly, in the aqueous filtrate proteins of metabolic processes and stress response mainly oxidoreductases, were identified. Successfully, ZnO and FeO NPs were synthesized and characterized by transmission electron microscopy, energy dispersive X-ray spectroscopy, dynamic light scattering, thermogravimetric, and FTIR analysis. FTIR revealed organic compounds in nanoparticles acting as probably capping agents. This research is the first report in which a proteomic analysis identifies multiple enzymes involved in the biogenic process of NP biosynthesis from T. harzianum, and its role is clearly demonstrated by the formation of zincite and magnetite nanoparticles.